The Implementation of Brand Element Strategic in Marketing Communication on Local Small-Medium Business in West Sumatra - Tuti Widiastuti (Ikatan Sarjana Komunikasi Indonesia, 2019)
In this study the authors want to provide an overview of the local small business brands that use brand strategy element in developing its business. This research has a focus of research on Kapuyuak brand which is a local brand originating from Bukittinggi West Sumatra. The thing studied is the attribute used by the Kapuyuak brand so that the public has a perception and become loyal to the brand. This study uses qualitative methods to obtain more in-depth information about the strategies used from Kapuyuak and its customers. The results show that Kapuyuak has the power to identify the value of the brand based on the insight of consumers and market insight. In communicating its brand Kapuyuak uses internet and social media in distributing its value.